Ingested metallic foreign body lodged in the appendix - R R Sarkar; J Bisht; S K Sinha Roy (Wolters Kluwer Medknow Publications, 2011)
An 8-year-old child ingested a metallic screw 3 months prior to admission. At laparotomy, the foreign body was found to be lodged inside the vermiform appendix, and was removed by appendicectomy.